(untitled) (Research, Society and Development, 2023)
The Conservation units consist of territorial spaces and their environmental resources, including jurisdictional waters, with relevant natural characteristics, with conservation objectives and defined limits, under the special administration regime, to which adequate protection guarantees are applied. Sometimes conservation units are inhabited by traditional peoples and in these places, these human groups organized by successive generations, seek subsistence based on sustainability and lifestyle through rural activities. These rural communities can legally obtain the concession of the real right of use as a guarantee of land regularization, formalizing the ownership of the land where they live and carry out the economic activity. Thus, the present research aims to analyze the real right of use as an instrument to guarantee the permanence of the traditional populations inhabitants in the lands comprised inside conservation unit, and thus, if this proves effective as a land regularization mechanism for the benefit of these communities, as well as whether this process can help to realize the socioeconomic development of these populations. The research was based on the case study method, with a qualitative approach, in the Tupé Sustainable Development Reserve. Therefore, it is expected with this work, to contribute to the knowledge and reflection about the researched elements, such as the territorial space, the human being, the environmental perception and the rights, in an interactive vision, which may be important in the search for solutions to the possible controversies presented through the conclusions obtained.